1990
DOI: 10.3109/02699059009026187
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation versus day treatment in head-injured adults: Is there an impact on emotional and psychosocial adjustment?

Abstract: Emotional and psychosocial adjustments are typically the most challenging problems faced by the head injured, but there exists a paucity in research as to how affective problems are best ameliorated. In the present analysis, emotional and psychosocial adjustment were evaluated as part of a study comparing the efficacy of cognitive remediation versus day treatment. Out of 24 head-injured patients, half were randomly assigned into either treatment condition, each conducted 4 days a week over an 8-week span. A mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Most of the reviewed studies based on this approach demonstrated improvements (i.e., internal validity or efficacy) in at least one dependent variable. However, due to the unsuccessful or equivocal outcomes reported in RCT-Class I and cohortClass II studies (Ruff and Niemann 1990;Medd and Tate 2000;Lincoln and Flannaghan 2003) combined with the negative or equivocal results raised from uncontrolled-Class III studies (Ownsworth and McFarland 2004;Swan and Alderman 2004;Dewar and Gracey 2007), it appears that interventions promoting internalizing of self-regulation strategies through self-instruction or self-monitoring and integrated treatment of individualized cognitive and interpersonal therapies should be considered as Practice Options for persons with impaired executive functioning and emotional self-regulation following TBI or stroke (see Table 4). These conclusions are similar to those reached in the reviews by Cicerone et al (2000Cicerone et al ( , 2005.…”
Section: Cognitive-behavior Therapymentioning
confidence: 99%
“…Most of the reviewed studies based on this approach demonstrated improvements (i.e., internal validity or efficacy) in at least one dependent variable. However, due to the unsuccessful or equivocal outcomes reported in RCT-Class I and cohortClass II studies (Ruff and Niemann 1990;Medd and Tate 2000;Lincoln and Flannaghan 2003) combined with the negative or equivocal results raised from uncontrolled-Class III studies (Ownsworth and McFarland 2004;Swan and Alderman 2004;Dewar and Gracey 2007), it appears that interventions promoting internalizing of self-regulation strategies through self-instruction or self-monitoring and integrated treatment of individualized cognitive and interpersonal therapies should be considered as Practice Options for persons with impaired executive functioning and emotional self-regulation following TBI or stroke (see Table 4). These conclusions are similar to those reached in the reviews by Cicerone et al (2000Cicerone et al ( , 2005.…”
Section: Cognitive-behavior Therapymentioning
confidence: 99%
“…This is consonant with findings which observed reduction in some emotional adjustment difficulties, even years after injury. 37 Such improvements may be due to the non-specific effects of attending a group. There was, however, a difference in mood between the restitution and compensation groups, as assessed on the Wimbledon Self Report Scale.…”
Section: Discussionmentioning
confidence: 99%
“…The KAS-P details the degree to which participants: (1) are able to complete chores and free-time activities; (2) whether this level of functioning meets their own expectations for each chore or activity; and (3) level of satisfaction with their current level of functioning. The KAS-P has adequate reliability (Ruff & Niemann, 1990), and has demonstrated sensitivity to changes in NP-related everyday functioning and life quality in patients who have traumatic brain injury (Klonoff, Snow, & Costa, 1986) and chronic obstructive pulmonary disease (McSweeny, Grant, Heaton, Adams, & Timms, 1982;McSweeny, Grant, Heaton, Prigatano, & Adams, 1985). Participants also completed the Patient's Assessment of Own Functioning Inventory (PAOFI; Chelune, Heaton, & Lehman, 1986), which is a 41-item questionnaire in which the participant reports the frequency with which he/she experiences difficul-ties in everyday life with various aspects of memory, language and communication, use of his/her hands, sensory-perception, and higher level cognitive and intellectual functions; additional questions asked about employment status and recreation activities.…”
Section: )mentioning
confidence: 99%